2013
DOI: 10.1016/j.semnephrol.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Gut Sensing of Potassium Intake and its Role in Potassium Homeostasis

Abstract: Extracellular K+ homeostasis has been explained by feedback mechanisms in which changes in extracellular K+ concentration drive renal K+ excretion directly or indirectly via stimulating aldosterone secretion. However, this cannot explain meal-induced kaliuresis that often occurs without increases in plasma K+ or aldosterone concentration. Recent studies have produced evidence supporting a feedforward control in which gut sensing of dietary K+ increases renal K+ excretion (and extrarenal K+ uptake) independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 63 publications
0
38
0
Order By: Relevance
“…These studies suggest that dietary K 1 intake through a splanchnic sensing mechanism can signal increases in renal K 1 excretion independent of changes in plasma K 1 concentration or aldosterone (reviewed in ref. 80).…”
Section: Enteric Sensor Of Kmentioning
confidence: 99%
“…These studies suggest that dietary K 1 intake through a splanchnic sensing mechanism can signal increases in renal K 1 excretion independent of changes in plasma K 1 concentration or aldosterone (reviewed in ref. 80).…”
Section: Enteric Sensor Of Kmentioning
confidence: 99%
“…The serum potassium level is normally maintained within a narrow range with little daily variation due to intricate renal and extrarenal mechanisms . Therefore, treatment of hypokalemia is critical for the health of the eating disorder patient, because of the widespread adverse clinical abnormalities that may follow in the wake of potassium depletion.…”
Section: Treatment Of Hypokalemiamentioning
confidence: 99%
“…Through this mechanism the enteric sensors may enhance the clearance of the K + from diet or infusion 3638 . A study has also suggested that dietary K + intake through a splanchnic sensing mechanism can signal increases in renal K + excretion independent of changes in plasma K + concentration or aldosterone 20 .…”
Section: Sources Of Potassiummentioning
confidence: 99%
“…High blood pressure can be influenced by the levels of plasma potassium, low potassium causes hypertension and increasing potassium intake lowers blood pressure 20,107 . The blood pressure of people with hypertension is lowered when they are given K + supplements.…”
Section: Hypertension and Potassium Homeostasismentioning
confidence: 99%
See 1 more Smart Citation